Plan de mejoramiento en la empresa Apuestas Ochoa, de la ciudad de Armenia-Quindío, con énfasis en la formulación, análisis y desarrollo de proyectos (2015)
The present paper is an improvement plan, chosen as graduation line for students of the University of Quindío, mentioned on the cover of the document, and taking advantage of the link made by the same company with betting Ochoa, a company dedicated to marketing and permanent sale of stakes in the Quindío, protected by law in January 1982, a full and detailed study of internal and external factors affecting the company, which can generate an improvement plan to mitigate those of these factors is performed, that they are not beneficial to the organization, looking potentiate those who maintain a solid and important maturity Betting Ochoa, his business chance in the Department. Thus, in the present project is broken down in detail and ordered each of these factors impact on the company, based on a global stage, to reach the inner, through studies to each of its areas, with to generate a situational diagnosis that triggers on strategies for optimal development of an objective solution, which seeks to create a project area within the organization, neutralize variables that could generate recession Betting Ochoa, a pioneer in the market for Betting on the Department and other associated services, play an important role in the economic development of Quindío paper.